Weight status in individuals with autism spectrum disorder: A study protocol for systematic review and meta-analysis. Issue 38 (September 2019) - Xie, Xue-Ni; Li, Yong-Jiang; Lei, Xue; Li, Ya-Min
Abstract: Background: Weight status and autism spectrum disorder (ASD) are rising public health concerns. An increasing number of reports indicate that individuals with ASD may have unhealthy weight status, but the evidence is mixed. To understand the weight status in individuals with ASD and provide strategies for prevention and intervention, we describe the protocol for a systematic review and meta-analysis aimed at assessing the prevalence of obesity, overweight, and underweight in ASD. Methods: A broad range of key bibliographic databases including MEDLINE (PubMed), Embase, Cochrane, and ISI Web of Science will be searched to identify studies reporting the prevalence of obesity, overweight, and underweight in patients with ASD. Retrieved records will be independently screened by 2 authors and relevant estimates will be extracted from studies reporting data on obesity, overweight, and underweight prevalence among individuals with ASD. The assessment of study quality will be conducted primarily using the Newcastle–Ottawa scale and checklist proposed by the Joanna Briggs Institute. Prevalence estimates of obesity and overweight will be separately pooled using random-effects model. The pooled estimates will be summarized and presented by regional groupings. Subgroup analysis will be conducted for variables (such as study setting, participants' age, and geographical region) across studies, depending on data availability. Between-study heterogeneity will be assessed using the I 2 statistic and explored through subgroup analyses. This systematic review and meta-analysis will be reported following the preferred reporting items for systematic reviews and meta-analyses checklist and the meta-analysis of observational studies in epidemiology statements guidelines for meta-analysis and systematic reviews of observational studies. Results: In this study, we will outline details of the aims and methods on the meta-analysis of weight status of individuals with ASD. Conclusion: The results of this study will summarize the current data of weight status of individuals with ASD. Registration: PROSPERO-National Institute of Health Research (NIHR) Prospective Register of Systematic Reviews (CRD42019130790). Abstract : Supplemental Digital Content is available in the text